The Indian Spice Turmeric Delays and Mitigates Radiation-Induced Oral Mucositis in Patients Undergoing Treatment for Head and Neck Cancer: An Investigational Study. (May 2014) - Rao, Suresh; Dinkar, Chetana; Vaishnav, Lalit Kumar; Rao, Pratima; Rai, Manoj Ponadka; Fayad, Raja; Baliga, Manjeshwar Shrinath
Purpose . Radiation-induced oral mucositis is an acute morbidity seen in patients undergoing treatment for head and neck cancers. In this study, we evaluated the efficacy of turmeric in preventing radiation-induced mucositis. Methods . This was a single-blinded, randomized, controlled clinical trial and was conducted with head and neck cancer patients requiring 70 Gy of radiation or chemoradiotherapy (daily radiotherapy plus carboplatin once a week). Eligible patients (n = 80) were randomly assigned to receive either turmeric gargle (n = 40) or povidone-iodine ([n = 40] active comparator condition) during chemo/radiotherapy during the period of treatment. Oral mucositis was assessed using the RTOG (Radiation Therapy Oncology Group) grading system before the start, during, and at the end of the treatment by an investigator unaware of the treatment. The primary endpoint of this study was the incidence of mucositis every week during the 7-week period. The secondary endpoint was the effect of turmeric gargle on the incidence of treatment breaks, loss of scheduled treatment days, and decrease in body weight at the end of the treatment. Results . This study clearly suggests that when compared with the cohorts using povidone-iodine gargle, the group using turmeric as a mouthwash had delayed and reduced the levels of radiation-induced oral mucositis and was statistically significant at all time points ( P < 0.001 to P < 0.0001). Additionally, the cohorts using turmeric had decreased intolerable mucositis ( P < 0.001) and lesser incidence of treatment breaks in the first half of the treatment schedule before 4 weeks ( P < 0.01) and reduced change in body weight ( P < 0.001). Conclusions . Gargling with turmeric by head and neck cancer patients undergoing radiation therapy provided significant benefit by delaying and reducing the severity of mucositis. Turmeric is readily available, relatively inexpensive, and highly accepted making it useful in cancer treatment.